Phospholipase Cζ (PLCζ) versus postacrosomal sheath WW domain‐binding protein (PAWP): Which molecule will survive as a sperm factor? - Nakai, Michiko (Anim Sci J, 2020)
During mammalian fertilization, sperm is fused with the oocyte's membrane, triggering the resumption of meiosis from the metaphase II arrest, the extrusion of the second polar body, and the exocytosis of cortical granules; these events are collectively called 'oocyte activation.' In all species studied to date, the transient rise in the cytosolic level of calcium (in particular, the repeated calcium increases called 'calcium oscillations' in mammals) is required for these events. Researchers have focused on identifying the factor(s) that can induce calcium oscillations during fertilization. Sperm‐specific phospholipase C, i.e., PLC zeta (PLCζ), is a strong candidate of the factor(s), and several research groups using different species obtained evidence that PLCζ is a sperm factor that can induce calcium oscillations during fertilization. However, postacrosomal sheath Tryptophan‐Tryptophan (WW)—domain‐binding protein (PAWP) was recently shown to have a pivotal role in inducing calcium oscillations in some species. In this review, we focus on PLCζ and PAWP as sperm factors, and we discuss this controversy: Which of these two molecules survives as a sperm factor?